1997
DOI: 10.1055/s-0038-1657631
|View full text |Cite
|
Sign up to set email alerts
|

D-Dimer Determination to Assess Regression of Deep Venous Thrombosis

Abstract: SummaryA number of studies evaluating deep venous thrombosis (DVT) have demonstrated that plasma levels of thrombotic and fibrinolytic parameters change during treatment, but the relationship between thrombus regression and evolution of these markers remains unknown. The objective of the present study was to correlate levels of D-Dimer (DD) with thrombus regression as assessed by duplex scanning.From 44 patients treated for acute DVT, DD were determined at diagnosis and at the end of initial heparin therapy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Eighty-seven patients had DVT and in them, it was clearly seen that D-Dimer concentrations were at their highest concentration on the second day from the diagnosis [5]. The time course analysis of D-Dimer has been shown to be a marker of thrombus resolution and high D-Dimer concentrations during the course of treatment and might identify patients with a non-resolving or slow resolving thrombus [6][7][8][9][10]. Therefore it is conceivable that the concentration of D-Dimer will follow an expected and accurate time course.…”
Section: Discussionmentioning
confidence: 99%
“…Eighty-seven patients had DVT and in them, it was clearly seen that D-Dimer concentrations were at their highest concentration on the second day from the diagnosis [5]. The time course analysis of D-Dimer has been shown to be a marker of thrombus resolution and high D-Dimer concentrations during the course of treatment and might identify patients with a non-resolving or slow resolving thrombus [6][7][8][9][10]. Therefore it is conceivable that the concentration of D-Dimer will follow an expected and accurate time course.…”
Section: Discussionmentioning
confidence: 99%
“…D-dimer levels are elevated in initial thrombus formation [41] and serve as an indicator of fibrinolysis [42]. In this study D-dimer levels were used as a supporting indicator of thrombus development and resolution.…”
Section: Discussionmentioning
confidence: 99%
“…In this study D-dimer levels were used as a supporting indicator of thrombus development and resolution. In opposition to TF, which is important in thrombus initiation [4-6], D-dimer plasma levels increase at later time points in thrombosis, during fibrinolysis [42] and thrombus resolution. We showed that, both the LysMCre positive and LysMCre negative mice showed a peak in D-dimer levels at day 2 post thrombosis, which decreased to baseline levels by day 6, despite a large thrombus burden.…”
Section: Discussionmentioning
confidence: 99%
“…While this is highly unlikely to affect the interpretation of imaging studies, it may affect the interpretation of D‐dimer assays. Several studies have shown a fall in D‐dimer levels following anticoagulation with heparins (Speiser et al , 1990; Janssen et al , 1997b; Stricker et al , 1999). Stricker et al (1999) demonstrated a significant fall in D‐dimer values in patients that were serially tested after commencing anticoagulation with heparin or low molecular weight heparin for VTE.…”
mentioning
confidence: 99%
“…Moreover, the D‐dimer level recorded on any 1 d in patients on nadroparin depended on the time of sampling with lower levels detected at times of peak heparin activity (Stricker et al , 1999). In a study of 44 patients treated with heparin for at least 5 d, changes in D‐dimer levels were observed that would have altered the interpretation of the assay performed as a screening test for excluding the diagnosis of VTE (Janssen et al , 1997b). There are few data on the effect of a single dose of heparin on the interpretation of D‐dimer assays for exclusion of a diagnosis of DVT.…”
mentioning
confidence: 99%